2023
DOI: 10.1108/ci-08-2022-0221
|View full text |Cite
|
Sign up to set email alerts
|

Construction and demolition waste management in Jordan: a multifaceted perspective

Abstract: Purpose The purpose of this study is to explore the multifaceted challenge of managing construction and demolition waste within the context of the Jordan construction industry. Design/methodology/approach Using data sourced through desk research, interviews and questionnaires, this study examines the principal causes of increased volumes of construction and demolition waste, as well as the obstacles to both developing and implementing better waste management strategies. Findings This study identifies multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The waste type and quantity in the construction sector are highly influenced by construction size, type, and technology used [11] while it is generated in different amounts during each project stage [12]. Researchers have found that CW multiplies due to design issues and errors, improper scheduling, reworks, lack of skilled labours, poor project management, materials storage and handling, and ill management of waste [5,[12][13][14][15]. Table 1 summarises the most common categorisations of construction waste.…”
Section: Construction Waste Generation 21 Causes Of Construction Wastementioning
confidence: 99%
See 3 more Smart Citations
“…The waste type and quantity in the construction sector are highly influenced by construction size, type, and technology used [11] while it is generated in different amounts during each project stage [12]. Researchers have found that CW multiplies due to design issues and errors, improper scheduling, reworks, lack of skilled labours, poor project management, materials storage and handling, and ill management of waste [5,[12][13][14][15]. Table 1 summarises the most common categorisations of construction waste.…”
Section: Construction Waste Generation 21 Causes Of Construction Wastementioning
confidence: 99%
“…Design-related Design complexity (W1) [3,15] Design documents errors (W2) [3,5,13,16] Design changes during construction (W3) [3,5,15] Poor coordination & communication (W4) [3,5,[12][13][14] Procurement-related Ordering errors (W5) [3,13,15] Buy low-quality materials (W6) [3,13,15] Human-related Lack of experienced designers (W7) [3,13,15] Lack of skilled workers (W8) [3,5,[13][14][15] Handling and Storage On-site transportation methods (W9) [3,13,15] Inappropriate storage (W10) [13][14][15] Site Conditions Leftover materials on site (W11) [3,13,15] Poor site condition (W12) [3,5,13,15] Management-related Inaccurate planning and scheduling (W13) [3,12,13,15] Incapable site supervision (W14) [3,13...…”
Section: Group Construction Waste Causes Referencesmentioning
confidence: 99%
See 2 more Smart Citations